2020
DOI: 10.1099/jgv.0.001416
|View full text |Cite
|
Sign up to set email alerts
|

Basic insights into Zika virus infection of neuroglial and brain endothelial cells

Abstract: Zika virus (ZIKV) has recently emerged as an important human pathogen due to the strong evidence that it causes disease of the central nervous system, particularly microcephaly and Guillain–Barré syndrome. The pathogenesis of disease, including mechanisms of neuroinvasion, may include both invasion via the blood–brain barrier and via peripheral (including cranial) nerves. Cellular responses to infection are also poorly understood. This study characterizes the in vitro infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“… 37 Similarly, after 10 days of exposure to Zika virus, brain endothelial cells (hCMECs) did not show a reduction in cell viability. 34 After a 6 day exposure to the Coxsackie virus, HUVECs did not respond with a change in their cell density, morphology or any other culture parameters investigated. 6 Overall, our data is generally in agreement with these prior reports and illustrates that a short duration exposure to SARS-CoV-2 structural proteins does not impair endothelial cell viability and density (with the exception of N-protein).…”
Section: Discussionmentioning
confidence: 86%
“… 37 Similarly, after 10 days of exposure to Zika virus, brain endothelial cells (hCMECs) did not show a reduction in cell viability. 34 After a 6 day exposure to the Coxsackie virus, HUVECs did not respond with a change in their cell density, morphology or any other culture parameters investigated. 6 Overall, our data is generally in agreement with these prior reports and illustrates that a short duration exposure to SARS-CoV-2 structural proteins does not impair endothelial cell viability and density (with the exception of N-protein).…”
Section: Discussionmentioning
confidence: 86%
“…SARS-CoV-2 infection has been associated with cytokine storm as a poor prognosis of disease progression ( Tay et al, 2020 ). Misbalance of cytokine levels in the CNS microenvironment is associated with several pathologies ( Guzman-Martinez et al, 2019 , Lima et al, 2019 , Mutso et al, 2020 , Sochocka et al, 2017 ), hence the need to uncover the brain inflammation associated with SARS-CoV-2 infection. To investigate if SARS-CoV-2 generates a direct inflammatory response in neural tissues, the supernatant of infected NP was collected at 5 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…This piece of evidence is in agreement with a recent study that found that the process of ZIKV crossing the hCMEC/D3 cell-monolayer was blocked by pharmacological inhibitors of endocytosis ( 41 ). Recent studies found that ZIKV establishes persistent infection in the BBB model cell line hCMEC/D3 ( 42 ). Interestingly, ZIKV infection fails to damage the hCMEC/D3 cells ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%